EFL students’ cooperation and creativity in using English grammar through poetry-based method - Suswati Hendriani; Martin Kustati (Proceedings of AICS - Social Sciences, 2017)
Cooperation and creativity are two main soft skills in the 21st century needed by future young generation. Without cooperation and creativity, it will be very difficult for them to survive in the next more challenging era. Therefore, it is the duty of English teachers to make the students be willing to cooperate with others and creative in their English language learning. One of the possible solutions is to use literature (poetry) in teaching English, including that of English grammar. This research is aimed at finding out whether poetry can foster students’ cooperation and creativity in using English Grammar or not. A qualitative research was conducted where the data taken from observation and documentation. To collect the data of cooperation, observation technique was used during the grammar teaching-learning process. Meanwhile, to collect the data of the students’ creativity, the poetries that were composed by them were analyzed in terms of contents, idea development, and vocabulary choice. The research results show that the cooperation among the students and their creativity was highly improved. The finding can be used as an alternative of teaching methods in teaching grammar.